Early miscarriage after single and double blastocyst transfer - Došen, Marko (Zdravniški vestnik, 2011)
Background: Occurrence of early miscarriage in pregnancies accomplished by in vitro fertilisation procedures was studied, almost exclusively, in women in whom cleavage stage embryos were transferred. The primary objective of our retrospective study was to identify the factors predicting early miscarriage following the transfer of one or two blastocysts. Materials and Methods: Using the multivariate logistic regression model, we analyzed the parameters of 1020 sequential IVF/ICSI cycles with the transfer of one or two blastocysts, in which positive levels of ßhCG were observed. Age of the patient, fertilization method, number of retrieved oocytes, number of developed, frozen and transferred blastocysts and their quality were analyzed as possible predictors for early spontaneous miscarriage. Results: The overall frequency of biochemical pregnancies in the observed group of patients was 6.6 % (67/1020). Biochemical pregnancies occurred somewhat more frequently following the transfer of one, rather than two blastocysts (9.05 % (23/254) vs. 5.8 % (44/763)). The rate of early clinical miscarriage was 13.3 % (136/1020), with the rate of miscarriage higher following the transfer of one as opposed to two blastocysts (15.3 % (39/254) vs. 12.7(97/763)). If biochemical pregnancies and early clinical miscarriages were observed together, the rate of early pregnancy losses in the overall sample studied was 19.9 % (203/1020), following the transfer of one blastocyst 24.4 % (62/254) and following the transfer of two 18.4 % (141/763). Using the multivariate logistic regression, we demonstrated that statistically significant predictors for early spontaneous miscarriages were the patient's age (OR = 1.098; 95 % CI 1.057-1.140, P < 0.001), the number of blastocysts transferred (OR = 0.592; 95 % CI 0.412-0.851, P = 0.005), the quality of blastocysts transferred (OR=0.666; 95 % CI 0.468-0.949; P = 0.024), as well as the number of blastocysts frozen (OR = 0.912; 95 % CI 0.832-0.999; P = 0.048). Conclusion: The transfer of optimal quality blastocyst(s) and transfer of two blastocysts were associated with a reduced rate of spontaneous miscarriages in pregnancies achieved by ART.
Keywords: Abortion, Spontaneous; Blastocista; blastociste; Blastocyst; fertilization; Fertilization in Vitro; in vitro fertilization; Injiciranje semena, intracitoplazmično; oploditev; Oploditev in vitro; oploditev z biomedicinsko pomočjo; prenos; Reproductive Techniques, Assisted; Reproduktivne tehnike, asistirane; Sperm Injections, Intracytoplasmic; Spontani splav